Open Data in cities. - Carrara, Wendy; Engbers, Wander; Nieuwenhuis, Margriet; Steenbergen, Eva van (My University, 2020)
Open Data is a valuable source for solving civic problems, improving transparency and closing the gap between local government and its citizens. The World Council on City Data introduced 17 different themes including around 100 indicators relating to the standardisation of city data. Urban planning is one of those focus areas of high value to most cities, as cities are facing considerable population growth that puts pressure on the municipality’s economy. The huge amount of data that cities gather can help solve those problems more efficiently. Transportation and emergency situations are other topics directly related to high population density in cities. Users can highly benefits from the development of mobile applications helping citizens and first responders to plan their journey using alternative routes if necessary. Cities are starting to look at the benefits of Open Data.
Keywords: Verwaltungsdaten; Planungsdaten; Basisdaten; Zugänglichkeit; Stadtverwaltung; Technische Infrastruktur; Versorgung; Bildung; Smart City; Städtevergleich; Open Data; Datennutzung; Datenbereitstellung